(untitled) (Research, Society and Development, 2021)
Objective: This study aims to verify the importance of diagnosing malocclusions, clinical implications and early treatment through preventive and interceptive orthodontics, addressing the benefits of using PLA and removing the habit of lip sucking through its use. Methodology: Based on the permission of the patient’s guardian through the Informed Consent Form (FICF) to share their image for the proper purpose, this study is a clinical case report of a descriptive analytical nature (Pereira et al., 2018 ). Case Report: Female patient, 12 years old, Pattern II due to mandibular and maxillary deficiency, with lip sucking, accentuated vestibularization of the upper incisors. The therapy resulted in elimination of the habit and improvement in upper incisor inclination. Avoiding future complex treatments, providing improvement and quality of life for the patient. Final Considerations: The deleterious oral habits are factors that lead to malocclusions in patients with mixed dentition. Active lip plaque was the interceptive treatment capable of eliminating the habit of lip sucking in a short period of time.